Effects of Cr addition on the constitutive equation and precipitated phases of copper alloy during hot deformation. (June 2020) - Ban, Yijie; Zhang, Yi; Jia, Yanlin; Tian, Baohong; Volinsky, Alex A.; Zhang, Xiaohui; Zhang, Qifei; Geng, Yongfeng; Liu, Yong; Li, Xu
Abstract: The Cu-Ni-Si alloy has widely applications in the lead frames and electronics industries due to its high strength and conductivity. In this work, hot deformation behavior of the Cu-1.5Ni-1.1Co-0.6Si and Cu-1.5Ni-1.1Co-0.6Si-0.1Cr alloys were investigated through the isothermal compression tests using the Gleeble-1500D thermo-mechanical simulator operating at the temperature ranging from 500 °C to 900 °C and 0.001–10 s −1 strain rate. The deformed microstructure was characterized by the electron backscatter diffraction (EBSD) and the transmission electron microscopy. The constitutive equations of the alloys were established. According to the microstructure analysis, it can be observed that the grain size of the alloy with Cr was more uniform. In addition, the misorientation angle of 14.19 during recrystallization was significantly lower than 24 after the recrystallization, which means that the migration rate of grain boundaries is slow. The texture of the Cu-Ni-Co-Si alloy at 800 °C is the Goss {011}〈100〉 texture and {001}〈100〉 cubic texture, while the Goss texture at 900 °C is replaced by the {011} 〈112〉brass texture. The effects of Cr on precipitation phases were analyzed, and the precipitated phases were (Ni, Co)2 Si, Co2 Si. The addition of Cr promoted precipitation and significantly reduced the precipitate size. The addition of Cr can improve the strength and activation energy of the alloy. The activation energy was 569.8 kJ/mol and 639.5 kJ/mol, respectively. Graphical abstract: Unlabelled Image Highlights: The addition of Cr can obtain more precipitates. The addition of Cr can inhibit the dynamic recrystallization of Cu-Ni-Co-Si alloy. The size of precipitated phase decreases obviously with the addition of Cr elements.